Factors related to surgical site infection in spinal instrumentation surgery: a retrospective study in Japan - Kazumasa Konishi; Hideto Sano; Yosuke Kawano; Takehiko Moroi; Takumi Takeuchi; Masahito Takahashi; Naobumi Hosogane (Asian Spine Journal)
Study Design A retrospective study. Purpose To identify factors involved in surgical site infections (SSIs) after spinal instrumentation surgery performed at a single institution. Overview of Literature SSIs after spinal instrumentation surgery are a serious complication. Despite reports on risk factors for SSIs in spine surgery, limited studies are related to spinal instrumentation surgery. Methods In total, 828 patients (338 males and 490 females; mean age, 65.0 years) who underwent spinal instrumentation surgery from 2013 to 2021 in Kyorin University School of Medicine were retrospectively investigated. Patients were divided into the SSI (group I) and non-SSI (group N) groups. Patient characteristics, comorbidity, laboratory, and surgical factors were investigated. Univariate analysis was performed for each item, and multivariate logistic regression analysis was performed for items with significant differences. Results Fifteen patients (1.85%) had SSIs. Univariate analysis revealed significant differences between groups I and N in history of steroid use, serum albumin, C-reactive protein, number of fixed vertebrae, and perioperative blood transfusion. Multivariate logistic regression analysis showed that a history of steroid use (odds ratio [OR], 5.38; 95% confidence interval [CI], 1.41–20.49; p=0.014), serum albumin (OR, 0.34; 95% CI, 0.13–0.84; p=0.020), and perioperative blood transfusion (OR, 5.85; 95% CI, 1.46–23.50; p=0.013) were independent risk factors for SSIs. Conclusions The results of this study indicate that preoperative nutritional intervention, appropriate management of anemia, and intraoperative and postoperative bleeding control may decrease the incidence of SSIs. However, this study has several limitations, including its retrospective design, analysis of a few SSI cases, and inclusion of various surgical approaches and disease types. Future studies that address these limitations are desirable.